A Multi-Site, Randomized, Parallel-Group, Controlled Trial of Virtually-Delivered Sahaj Samadhi Meditation for the Management of Moderate Depressive Symptoms in Chronic Pain - Cheng DK; Simpson R; Moineddin R; Katz J; Mulsant BH; Vasudev A; Greiver M; Hosseiny F; Inzitari M; Newman RI; Rivlin​ L; Foat KD; et al. (Journal of Pain Research, 2025)
Darren K Cheng,1 Robert Simpson,2– 5 Rahim Moineddin,6 Joel Katz,7– 9 Benoit H Mulsant,10,11 Akshya Vasudev,12 Michelle Greiver,6,13 Fardous Hosseiny,14 Marco Inzitari,15,16 Ronnie I Newman,17,18 Leon Rivlin,19 Kirk D Foat,1 Andrea D Furlan,2,4 John Francis Flannery,2,4 Deanna Telner,6,20 Rachael Bosma,21 Michelle Naimer,6,22 Chadwick Chung,23 Andrew D Pinto,6,24– 26 Michelle LA Nelson,1,26,27 Ross Upshur,1,6,26 Abhimanyu Sud6,28 1Lunenfeld-Tanenbaum Research Institute, Sinai Health, Toronto, ON, Canada; 2Toronto Rehabilitation Institute, University Health Network, Toronto, ON, Canada; 3Sunnybrook Research Institute, Toronto, ON, Canada; 4Temerty Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 5Institute of Health and Wellbeing, University of Glasgow, Glasgow, Scotland; 6Department of Family and Community Medicine, Temerty Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 7Department of Psychology, York University, Toronto, ON, Canada; 8Department of Anesthesia and Pain Management, Toronto General Hospital, Toronto, ON, Canada; 9Department of Anesthesiology & Pain Medicine, University of Toronto, Toronto, ON, Canada; 10Department of Psychiatry, University of Toronto, Toronto, ON, Canada; 11Centre for Addiction and Mental Health, Toronto, ON, Canada; 12Medpoint Clinic, London, ON, Canada; 13Department of Family and Community Medicine, North York General Hospital, Toronto, ON, Canada; 14Atlas Institute for Veterans and Families, Ottawa, ON, Canada; 15REFiT Research Group, Parc Sanitari Pere Virgili and VHIR, Barcelona, Catalonia, Spain; 16Faculty of Health Sciences and eHealth Lab, Open University of Catalonia (UOC), Barcelona, Catalonia, Spain; 17Art of Living Foundation, Fort Lauderdale, FL, USA; 18Nova Southeastern University Lifelong Learning Institute, Fort Lauderdale, FL, USA; 19Emergency Medicine, Humber River Health, Toronto, ON, Canada; 20South East Toronto Family Health Team, Toronto, ON, Canada; 21Toronto Academic Pain Medicine Institute (TAPMI), Women’s College Hospital, Toronto, ON, Canada; 22Department of Family Medicine, Sinai Health, Toronto, ON, Canada; 23Canadian Memorial Chiropractic College, Toronto, ON, Canada; 24Upstream Lab, MAP Centre for Urban Health Solutions, Li Ka Shing Knowledge Institute, Unity Health, Toronto, ON, Canada; 25Department of Family and Community Medicine, St. Michael’s Hospital, Toronto, ON, Canada; 26Division of Clinical Public Health, Dalla Lana School of Public Health, University of Toronto, Toronto, ON, Canada; 27Institute of Health Policy, Management and Evaluation, University of Toronto, Toronto, ON, Canada; 28Research Institute, Humber River Health, Toronto, ON, CanadaCorrespondence: Abhimanyu Sud, Department of Family and Community Medicine, Temerty Faculty of Medicine, University of Toronto, 500 University Avenue, 5th Floor, Toronto, ON, M5G 1V7, Canada, Email abhimanyu.sud@utoronto.caBackground: Chronic pain (CP) often co-occurs with depression, but promising scalable interventions have been under-investigated. We assessed the effectiveness of the virtually-delivered Sahaj Samadhi Meditation (SSM) program in reducing depressive symptoms in people with CP and moderate depressive symptoms.Methods: We conducted a randomized controlled trial comparing SSM to the Health Enhancement Program (HEP), an active control. Participants were recruited from multiple sites in the Greater Toronto Area and virtually. Both 12-week programs were delivered virtually in groups by appropriately trained facilitators. Depressive symptoms were assessed using the Patient Health Questionnaire (PHQ-9) at baseline, 12 weeks, and 24 weeks. ClinicalTrials.gov registration number: NCT04039568.Results: Of 108 participants enrolled, 89 were randomized to SSM (n=43) or HEP (n=46). Between-group differences for the PHQ-9 were not significant. Within-group mean differences for SSM were significant and greater than the minimal clinically important difference at both 12 weeks and 24 weeks (− 3.97 (95% CI − 6.69 to − 1.24) and − 4.96 (− 8.36 to − 1.56), respectively), while within-group mean differences were not significant for HEP.Conclusion: This study suggests potential benefits of SSM for individuals with comorbid CP and depression. Future trials should include larger sample sizes in non-pandemic conditions to better evaluate the effectiveness of SSM. Further research should also explore pragmatic trial designs and the integration of mind-body interventions in clinical settings.Keywords: chronic pain, depressive disorder, mind-body therapies, meditation, clinical trial